Unpacking musical beauty: Sound, emotion, and impact differences across expertise and personality - Yuko Arthurs; Eve Merlini; Diana Omigie (PLoS ONE, 2025)
Beauty is an aesthetic quality that many composers and performers strive to attain and that most listeners value highly in music. Yet, what listeners hear and feel when they find music beautiful, the impact this experience has on them, and wherein lie any potential individual differences remain unclear. To address these gaps, an online questionnaire was administered to 81 adults. They described their experience of listening to three self-selected “beautiful pieces of music” alongside three pieces they listened to a lot but did not consider beautiful; focusing on each piece’s sonic features, emotions induced, and any impact engaging with the pieces had had on them. Respondents’ personality traits and level of musical training were also collected to explore if these contributed significantly to variability in the data. Thematic analysis of text responses showed that participants consider intrinsic features of the music (mellow timbre, pleasing melodies and harmonies, slow tempo), cognitive factors (degree of change, complexity levels, and repetition), and aesthetic criteria (emotional effects, presence of a message, expressivity) when judging the beauty of a piece. It also showed that, beyond being calming and evoking pleasant sadness, pieces perceived as beautiful tend to move, transport and emotionally resonate with the listener, inspiring musical activities, and providing strong emotional support. Exploratory, quantitative analyses revealed that amateur musicians and open individuals reported a wider range of contributing musical features, while both amateur and professional musicians, along with conscientious individuals, reported a broader range of musical beauty’s influence on their musical activities. Our study suggests that musical beauty is a multifaceted phenomenon that has profound emotional impact on most individuals, while also displaying notable sensitivity to listeners’ personality and musical background. In doing so, our study contributes to a more comprehensive account of what it means to experience beauty in music.